2018
DOI: 10.1002/ajmg.a.40473
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Müllerian hormone levels in patients with turner syndrome: Relation to karyotype, spontaneous puberty, and replacement therapy

Abstract: Most girls with Turner syndrome (TS) suffer from incomplete sexual development, premature ovarian failure, and infertility due to abnormal ovarian folliculogenesis. Serum anti-Müllerian hormone (AMH) levels reflect the ovarian reserve in females, even in childhood. Thus, we aimed to assess serum AMH levels in girls with TS and its relation to karyotype, spontaneous puberty, and growth hormone (GH) therapy. Fifty TS were compared to 50 age- and sex-matched controls. All subjects were subjected to history, anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Our results remain in accordance with another studies with the frequency of spontaneous puberty in TS patients of about 50% [4,19]. In contrast there are also authors noticing lower percentage of spontaneous puberty in this group of patients [23][24][25]. Undoubtedly recognition of non-full-blown forms of TS will be growing thanks to the availability of karyotyping, so it may reveal noticeably increased prevalence of spontaneous puberty.…”
Section: Discussionsupporting
confidence: 92%
“…Our results remain in accordance with another studies with the frequency of spontaneous puberty in TS patients of about 50% [4,19]. In contrast there are also authors noticing lower percentage of spontaneous puberty in this group of patients [23][24][25]. Undoubtedly recognition of non-full-blown forms of TS will be growing thanks to the availability of karyotyping, so it may reveal noticeably increased prevalence of spontaneous puberty.…”
Section: Discussionsupporting
confidence: 92%
“…Third, in the current study, we did not measure serum anti‐Mullerian hormone (AMH) levels, inhibin B levels or the number of ovarian follicles on ultrasonography, which are thought to be predictors of the ovarian follicle reserve 26 . Hamza et al assessed serum AMH levels in 12 TS patients and its relationship with the karyotype and reported that the lowest measurable AMH level was in patients with a karyotype of 45, X 27 . Lastly, in the current study, we defined irregular menstruation as FSH levels < 25 IU/L with spontaneous menstruation more than 38 days apart and accompanied by progestin‐induced withdrawal bleeding.…”
Section: Discussionmentioning
confidence: 87%
“…At our knowledge, this is the first case of Xq duplication reporting assessment of AMH value, which is actually recognized to be the best marker of ovarian reserve in general population [35]. For these reasons, it has been proposed as a marker for early detection of ovarian failure in particular conditions such as, among others, Turner Syndrome [36][37][38]. Therefore, because of her risk of POI onset, a close monitoring of ovarian activity in this patient is needed [38].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it has been proposed as a marker for early detection of ovarian failure in particular conditions such as, among others, Turner Syndrome [36][37][38]. Therefore, because of her risk of POI onset, a close monitoring of ovarian activity in this patient is needed [38]. Periodically evaluation recording menses characteristics and hormonal dosages are required for early detection and treatment with hormonal replacement therapy for endogenous estrogenic deficiency.…”
Section: Discussionmentioning
confidence: 99%